1999
DOI: 10.1042/cs19980182
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system dysfunction in sclerodermic and primary Raynaud’s phenomenon

Abstract: Our aim was to investigate the sympathetic hyperactivity of systemic sclerosis that may lead to greater morbidity and mortality from cardiovascular events. We analysed the sympathetic (low-frequency) and vagal (high-frequency) components of heart rate variability, in supine and upright positions, in 10 patients with systemic sclerosis, 12 patients with primary Raynaud's phenomenon and 14 controls. We also analysed lung function in order to evaluate a possible link between heart rate variability and ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…However, in the frequency domain analysis, the HF power is affected more than LF power, which results in significant increase of HF/LF ratio that provides information on the sympathovagal imbalance in the SSc group. This further indicates a predominance of sympathetic nervous activity in these patients, which was previously found by other investigators, and which could partly explain the higher incidence of atrial and ventricular arrhythmias in the SSc subjects.…”
Section: Discussionsupporting
confidence: 87%
“…However, in the frequency domain analysis, the HF power is affected more than LF power, which results in significant increase of HF/LF ratio that provides information on the sympathovagal imbalance in the SSc group. This further indicates a predominance of sympathetic nervous activity in these patients, which was previously found by other investigators, and which could partly explain the higher incidence of atrial and ventricular arrhythmias in the SSc subjects.…”
Section: Discussionsupporting
confidence: 87%
“…One group has reported increased sympathetic activity in SSc patients in the supine position [40]. However, this increase was based on the normalized value of the sympathetic activity rather than the absolute value, which was in fact decreased similarly to our results and others.…”
Section: Discussionsupporting
confidence: 76%
“…Another group has reported a decrease in all HRV parameters in SSc patients in the time but not the frequency domain [35]. Other studies have not demonstrated a significant difference in the sympathovagal balance in SSc patients compared to normal controls, under baseline conditions [36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 98%
“…Decreased HRV with dominant vagal impairment has been found in individuals with coronary artery disease [26] or acute myocardial infarction [27], and in both clinical settings this condition is associated with an adverse prognosis. A profound decrease in HRV total power has been found in individuals with scleroderma, and this was accompanied by sympathetic predominance [28].…”
Section: Discussionmentioning
confidence: 99%